Controlled bottom-up synthesis and characterization of crystalline and amorphous lead(II) coordination polymers: Sonochemical methods, structure–property relationship, and photocatalytic applications - Saeedeh Ebad Sichani; Mohammad Jaafar Soltanianfard; Alison Zamanpour; Payam Hayati; Jan Janczak; Zahed Karimi-Jaberi (Ultrasonics Sonochemistry)
The 3D coordination polymers of lead (II) [Pb4(O)(L)3(H2O)]n, where H2L = C6H4(CO2H)2 (benzene-1,3-dicarboxylic acid), were synthesized in crystalline (1(a, b)) and amorphous (2(a, b)) phases. Hydrothermal and branch tube methods were used to self-assemble lead (II) from the bottom up to create the crystalline phases. Single-crystal X-ray diffraction (SC-XRD) was used to investigate two crystallized metal–organic frameworks (MOFs) with the same space group and chemical formula (P21/c). Through controlled green sonochemical methods, an ultrasonic bath and a probe homogenizer were used to prepare nano [Pb4(O)(L)3(H2O)]n in the amorphous phase. An extensive study has been conducted on the effect of initial reagent concentration, ultrasonic power, temperature, reaction time, and surfactant presence on the size and morphology of synthesized nanocoordination polymers. Analyses of the synthesized compounds were performed using scanning electron microscopy (SEM), powder X-ray diffraction (PXRD), FT-IR spectroscopy, and CHNS elemental analysis. By using thermal gravimetry (TGA-DTA), the thermal stability of nanostructures was examined and compared with that of crystalline structures. A Hirschfeld surface and a two-dimensional fingerprint diagram were used to analyze intermolecular interactions in crystalline phases. Photocatalytic degradation of methylene blue was investigated using 1a and 2b_2, which represent the synthetic compounds. Calculation of the band gap of synthesized polymers was conducted using the Tauc diagram (based on the DRS results). During optimal conditions of C0 = 0.6 mg L1, pH = 7, and irradiation time = 60 min, the maximum photodegradation efficiencies of methylene blue (MB) were observed for 1a and 2b_2. In terms of degradation efficiency, 1a’s reusability was 73.5 % for the first cycle and 70.6 % for the fifth, while 2b_2′s reusability was 88.2 % for the first cycle and 81.7 % for the fifth. These materials can be used in multiple photocatalytic cycles based on the results obtained.